Implementasi Beragama Di Era Digital Pada Generasi Z Sebagai Upaya Preventif Intoleran di Indonesia - Putri, Nurul Wulandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2023)
The problem of intolerance in Indonesia is starting to show a different pattern. Starting from the desecration of religious symbols, religious figures, places of worship and various other patterns, cases related to intolerance in Indonesia often occur, especially during political times like today, where making the slightest difference will cause problems. The purpose of this scientific work is to describe how to implement religious moderation in the digital era in Generation Z. This research uses a qualitative research approach, where research and understanding are based on methods that investigate social phenomena and human problems. In this research, researchers create a complex picture, examine words, detailed reports and conduct studies in natural situations. The data source used is secondary data obtained from document studies and journals related to this research. The conclusion in this case is that the implementation of religious moderation in this digital era is very supportive so that this form of religious moderation can be socialized properly and correctly, both through offline and online socialization. Generation Z is a generation that is aware of social media, where it is very easy for them to communicate and spread things, so it is necessary to have a role for Generation Z so that this attitude of intolerance can be suppressed through socialization on social media.